2007
DOI: 10.1371/journal.pgen.0030106
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Crossover Distributions and Variations in Interference Level along Arabidopsis thaliana Chromosome 4

Abstract: In many species, sex-related differences in crossover (CO) rates have been described at chromosomal and regional levels. In this study, we determined the CO distribution along the entire Arabidopsis thaliana Chromosome 4 (18 Mb) in male and female meiosis, using high density genetic maps built on large backcross populations (44 markers, >1,300 plants). We observed dramatic differences between male and female map lengths that were calculated as 88 cM and 52 cM, respectively. This difference is remarkably parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
96
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 70 publications
(70 reference statements)
12
96
1
Order By: Relevance
“…Interference values were estimated by three-point analysis for each arm of linkage group II, with results suggesting that it was higher for one arm (0.73) than for the other (0.53). Such variation of interference level between different parts of the genome has also been observed in Arabidopsis (Drouaud et al, 2007), in human (Lian et al, 2008) and in mouse (Broman et al, 2002).…”
Section: Origin Of 2n Gamete-producing Triploids In Citrusmentioning
confidence: 66%
“…Interference values were estimated by three-point analysis for each arm of linkage group II, with results suggesting that it was higher for one arm (0.73) than for the other (0.53). Such variation of interference level between different parts of the genome has also been observed in Arabidopsis (Drouaud et al, 2007), in human (Lian et al, 2008) and in mouse (Broman et al, 2002).…”
Section: Origin Of 2n Gamete-producing Triploids In Citrusmentioning
confidence: 66%
“…Studies in several plants and animals have shown that the average number of COs in meiosis may vary between male and female meiosis (see review by Lenormand and Dutheil 2005), but there is no general rule that governs the direction or degree of CO number variation. Similarly, the distribution of COs along chromosomes can also differ when comparing male and female meiosis (Drouaud et al 2007). Such distributions are generally nonuniform: some portions of the physical chromosome seem more likely to recombine while others hardly ever do (e.g., close to the centromere: Jones 1984; Anderson and Stack 2002).…”
mentioning
confidence: 99%
“…Second, different interval sizes were pooled together to gain statistical power, introducing biases. It is thus worthwhile to see whether the modeling approach (based on fitting parameters of CO formation models rather than on measuring coefficients of coincidence) gives results similar to those of Drouaud et al (2007) while adding more insight. A first step in this direction was provided by Giraut et al (2011) using the single pathway gamma model.…”
mentioning
confidence: 99%
See 2 more Smart Citations